Determinants of anemia among 6–59 months aged children in Bangladesh: evidence from nationally representative data. Issue 1 (December 2016) - Khan, Jahidur; Awan, Nabil; Misu, Farjana
Abstract Background Anemia is a global public health problem but the burden of anemia is disproportionately borne among children in developing countries. Anemia in early stages of life has serious consequences on the growth and development of the children. We examine the prevalence of anemia, possible association between anemia and different socio-economic, demographic, health and other factors among children with ages from 6 to 59 months from the nationally representative 2011 Bangladesh Demographic and Health Survey (BDHS). Methods Data on hemoglobin (Hb) concentration among the children aged 6–59 months from the most recent BDHS (2011) were used. This nationally representative survey allowed a multistage stratified cluster sampling design and provided data on a wide range of indicators such as fertility, mortality, women and child health, nutrition and other background characteristics. Anemia status was determined using hemoglobin level (<11.0 g/dl), and weighted prevalence of childhood anemia along with 95 % confidence intervals were provided. We also examined the distribution of weighted anemia prevalence across different groups and performed logistic regression to assess the association of anemia with different factors. Results A total of 2171 children aged 6–59 months were identified for this analysis, with weighted prevalence of anemia being 51.9 % overall- 47.4 % in urban and 53.1 % in rural regions. Results of a multivariable logistic regression analysis showed that, children below 24 months of age (odds ratio, [OR] 3.01; 95 % confidence interval [CI] 2.38-3.81), and those from an anemic mother (OR 1.80; 95 % CI 1.49-2.18) were at higher risk of anemia. Childhood anemia was significantly associated with chronic malnutrition of child, source of drinking water, household wealth and geographical location (defined by division). Conclusions A high prevalence of anemia among 6–59 months aged children was observed in Bangladesh. Given the negative impact of anemia on the development of children in future, there is an urgent need for effective and efficient remedial public health interventions.